A novel iron phosphate/oxygen hybrid cathode with high power output for the aprotic lithium-oxygen battery. (November 2017) - Zhu, Ding; Li, Wei; Wang, Ting; Mu, Shijia; Ding, Zhendong; Zhang, Kaifang; Chen, Yungui
Graphical abstract: Highlights: This study affords a new strategy to improve the power output of Li-O2 cell. FePO4 @C nanorods with exposed 010 facets are prepared and applied in O2 cathode. Hybrid cathode retains high energy output via ORR. Hybrid cathode attains 8-fold increased power output via Li + -insertion of FePO4 . Abstract: The aprotic lithium-oxygen (Li-O2 ) battery has recently attracted the worldwide attention by virtue of its super-large energy output. However, the extremely poor power output is one of the key issues which severely restrict the commercialization of the Li-O2 technology. In this work, we demonstrate a novel and simple strategy to address the power issue of the aprotic Li-O2 battery. An iron phosphate/oxygen (FePO4 /O2 ) hybrid cathode is proposed for the first time by simply introducing the 010-oriented FePO4 nanorods into a conventional O2 cathode. The as-built hybrid cathode not only retains a high-energy output via the O2 cathodic reaction, but also achieves an 8-fold increased power output via the Li + -insertion reaction of the 010-oriented FePO4 nanorods.